Media Informasi Ragam Jenis Makanan Tradisional Khas Lombok Berbasis Mobile - Rezky Ramdhaningsih; Dian Syafitri Chani Saputri; Syahroni Hidayat; Abdurahim Abdurahim (Puslitbang Sekawan Institute Nusa Tenggara, 2019)
Lombok has a variety of traditional Lombok foods that must be preserved. Traditional Lombok foods are one of the characteristics and treasures of culture owned by Indonesia, not only in terms of taste, form, and variety, but also from diverse colors. Lombok has considerable tourism potential, as one of the centers of culinary tourism destinations. However, promotional media and information are still limited, so this research want to introduce or promote traditional Lombok foods with easily and quickly by utilizing mobile-based technology. Making information media on various of traditional foods of Lombok with 2 languages, Indonesian and English. While the method used in multimedia development was Luther Sutopo. The steps are Concept, Design, Material Collecting, Assembly, Testing, Distribution. The tools used in making these mobile applications are Adobe flash and Adobe Photoshop. The results of this research is a Media Application for Variety of Traditional Foods of Lombok